METFORMIN DURING ADOLESCENCE ATTENUATES METABOLIC MARKERS IN ADULT RATS OVERFED DURING LACTATION (Arquivos do Mudi, 2023)
The growing prevalence of obesity around the world requires a better understanding of thispathophysiology and strategies to mitigate its deleterious effects. Obesity, related to lifestyle,is also associated with the DOHAD concept or ontogenetic plasticity. On the other hand, theadministration of certain drugs in critical periods of development can inhibit or reverse thissituation. This study aims to evaluate the effects of metformin treatment during adolescenceon the metabolism of overfed rats during lactation. For this purpose, the litters werestandardized in 9 pups until the 3rd day of life, and later adjusted in Normal Litters (NL, 9pups), and Reduced Litters (SL, 3 pups). At 30 days of age, they were subdivided into 4 newgroups: NL-saline gavage (NL-S), NL-metformin gavage (NL-M), SL-saline gavage (SL-S)and SL-metformin gavage (SL-M). Metformin treatment (300 mg/kg body weight) was givendaily during adolescence (PN30-PN60). At the end of lactation (PN21), SL animals presenteda greater body mass and abdominal size. In contrast, at 120 days old, SL-M rats exhibitedbetter peripheral insulin sensitivity, oral glucose tolerance, visceral adiposity, and lipid profilecompared to SL-S rats. Metformin did not alter the metabolism of NL animals. In conclusion,treatment with metformin during adolescence, in rats induced obesity by the litter reductionmodel, was effective in attenuating signs of obesity and/or metabolic syndrome, as well asrestoring the glycemic homeostasis of these animals to levels similar to equivalent controls.